PERANCANGAN GEOMETRI DAN POWER PENGADUK UNTUK BIOREAKTOR - Novio Valentino; Dwi Lukman Hakim; Fusia Mirda Yanti (Jurnal Energi dan Lingkungan (Enerlink), 2020)
Sei Pagar's palm oil mill (PKS Sei Pagar), PTPN V Riau processes fresh fruit bunch into crude palm oil(CPO). This processing also generates waste like empty fruit bunches (EFB), shells, fiber, and palm oilmill effluent (POME). POME has a high content of chemical oxygen demand (COD), approximately30,000-80,000 mg/L, which is usually fermented by bacteria. This fermentation mechanism can beused to produce biogas containing methane in a continuous stirred tank reactor (CSTR). Since POMEor organic materials for biogas production generally contain sludge, the biogas production processshould have an agitator to mix sediment in the base reactor and improve biogas production. Thisresearch aims to determine the agitator's specifications for the biogas pilot plant in PKS Sei Pagar,consisting of power type and type of stirrer include diameter calculation, geometry, and powercalculation. The agitator's power and geometry are determined based on input data from the datasheetreactor and the efficiency of the stirrer is calculated by Reynolds reynolds numbers. From thisresearch's calculations, an agitator geometry for the biogas pilot plant in PKS Sei Pagar had a length of0.875 m, a width of 0.7 m, and a height of 3.5 m. This research also obtained that the motor power resultwas 23.55 HP. The selection of motor power in the Biogas pilot plant's stirring process in PKS Sei Pagarshould have a standard agitator motor power of 25 HP.